Analisis Kondisi Sarana dan Prasarana dalam Mendukung Efektivitas Manajemen Pengelolaan Limbah Medis Padat B3 di RSUD Kabupaten Fakfak - Mertikatiga Halibi; Saraswati Prabawardani; Meike Meilan Lisangan (Mandalika Institute, 2026)
This study analyzes the role of facilities and infrastructure in supporting the effectiveness of hazardous and toxic medical solid waste management at Fakfak Regional General Hospital. The study used a mixed methods approach with an explanatory sequential design. Quantitative data were collected through field observation based on the criteria of the Ministry of Environment and Forestry Regulation Number P.56/MENLHK SETJEN/2015. Qualitative data were obtained through in depth interviews with hospital management, sanitation officers, room heads, cleaning service staff, and representatives of the environmental agency. The findings show that Fakfak Regional General Hospital has implemented the main stages of medical solid waste management, including segregation, containment, internal transportation, temporary storage, and treatment. However, several facilities have not fully complied with regulatory standards. The main problems include damaged waste bins and transport trolleys, limited availability of yellow infectious waste bags, inconsistent labeling, incomplete use of personal protective equipment, waste accumulation in temporary storage, an incinerator without an operational permit, and the absence of cooperation with licensed third party waste transporters. These findings indicate that the effectiveness of medical solid waste management is influenced by facility readiness, infrastructure adequacy, staff compliance, supervision, budgeting, licensing, and managerial coordination. Strengthening facilities and infrastructure, improving staff capacity, completing licensing requirements, and establishing cooperation with licensed waste transporters are therefore needed to support safe, effective, and sustainable medical waste management at Fakfak Regional General Hospital.